RISK FACTORS AND INCIDENCE OF MYOCARDIAL DAMAGE IN PATIENTS WITH HEMOBLASTOSIS RECEIVING ANTHRACYCLIN ANTIBIOTICS - N. T. Vatutin; E. V. Sklyannaya; M. A. El-Khatib; I. A. Sologub (Онкогематология)
Introduction. The anthracycline antibiotics cause clinically significant manifestations of cardiotoxicity (СТ) – myocardial injuries, reducing both quality and life expectancy of the oncological patients.The purpose of the study was to evaluate the incidence and risk factors anthracycline-induced СТ in patients with hemoblastosis.Materials and methods. The study included 131 case histories of patients with hemoblastosis, treated with anthracyclines. Patients were divided into two groups according to age – the 1st group involved 77 patients aged from 18 up to 50 years (average age of 25.6 ± 3.4 years), the 2nd – 54 patients aged from 51 up to 75 years (average age of 56.8 ± 4.6 years). At the first investigation phase we studied the incidence of anthracycline-induced СТ in various age groups patients. The second phase devoted to studying potential risk factors (a cumulative dose more than 240 mg/m2, a female, an age, the accompanying application of mediastinal radiation therapy or other cardiotoxic drugs, cardioprotection absence) influence on anthracycline-induced CD frequency.Results. The incidence of CT in young patients was 38.2% (95% confidence interval (CI) 25.6–51.6%), among the older age group – 14.3% (95% CI 5.3–26.7%). The incidence of CT is significantly higher among young people (χ2  = 5.63, p = 0.018). According to the results of univariate regression analysis, significant risk factors for the development of myocardial damage in patients with CT signs were: age <50 years – the odds ratio (OR) 2.69; 95% CI 1.05–6.84; the cumulative anthracycline dose more than 240 mg/m2  by doxorubicin (OR 5.17, 95% CI 1.38–27.55)  and the absence of prophylactic cardioprotective therapy (OR 23.38, 95% CI 6.49–84.14 ). In multivariate regression analysis independent risk factors for myocardial damage development were only the cumulative anthracyclines dose more than 240 mg/m2  (OR 6.17, 95% CI 1.32–28.71)  and the absence of prophylactic cardioprotective therapy (OR 2.82, 95% CI 1.09–7.28).Conclusions. Statistically significant higher anthracycline-induced cardiotoxicity frequency appeared in young patients. Reliable (р <0.05) cardiotoxicity risk factors were cumulative dose more than 240 mg/m2  and cardioprotection absence.